Highlighting mathematical and physico-chemical concepts which can generate epistemological obstacles in biology courses: A case study of ecology. - Zghida, Nour-eddine; Ben Ouahi, Mhamed; Saufi, Hamid; Najib, Soukaina Chaer; Chat, Mouad (SHS Web of Conferences, 2025)
Many biology content areas require physics, mathematics and chemistry, for example ecology, genetics, biochemistry and many other biology subject areas need mathematical algorithms and statistics. Several national and international tests confirmed that Moroccans students' performance in biology is low. Our research aims to identify some mathematical and physico-chemical concepts which can generate epistemological obstacles in understanding and acquiring ecology courses among high school students. Our research was conducted by mixed methods research who combines elements of quantitative and qualitative research. The population of the current research constituted from secondary high school teachers. Our sample is composed from a group of 60 life and earth sciences high school teachers. The data were collected by administering a questionnaire individually to 60 Moroccan secondary school teachers who they were asked in the written questionnaire. The data were analysed by SPSS23 and Excel package programs were used in data analysis. This research highlighted that ecology course is richer in mathematical and physico-chemical concepts which can generate epistemological obstacles (permeability, soil texture, porosity, water retention capacity, pressure, pH, energy, etc.). We found, also, that some mathematical concepts (Frequency, abundance, average, etc...) generate epistemological obstacles. Furthermore, these concepts are more presented in ecology course which can hinder students' understanding and acquiring.